Insecticide treated curtains and residual insecticide treatment to control Aedes aegypti: An acceptability study in Santiago de Cuba. - Dennis Pérez; Patrick Van der Stuyft; María Eugenia Toledo; Enrique Ceballos; Francisco Fabré; Pierre Lefèvre (Public Library of Science (PLoS), 2018)
Within the context of a field trial conducted by the Cuban vector control program (AaCP), we assessed acceptability of insecticide-treated curtains (ITCs) and residual insecticide treatment (RIT) with deltamethrin by the community. We also assessed the potential influence of interviewees' risk perceptions for getting dengue and disease severity.We embedded a qualitative study using in-depth interviews in a cluster randomized trial (CRT) testing the effectiveness of ITCs and RIT in Santiago de Cuba. In-depth interviews (N = 38) were conducted four and twelve months after deployment of the tools with people who accepted the tools, who stopped using them and who did not accept the tools. Data analysis was deductive. Main reasons for accepting ITCs at the start of the trial were perceived efficacy and not being harmful to health. Constraints linked to manufacturer instructions were the main reason for not using ITCs. People stopped using the ITCs due to perceived allergy, toxicity and low efficacy. Few heads of households refused RIT despite the noting reasons for rejection, such as allergy, health hazard and toxicity. Positive opinions of the vector control program influenced acceptability of both tools. However, frequent insecticide fogging as part of routine AaCP vector control actions diminished perceived efficacy of both tools and, therefore, acceptability. Fifty percent of interviewees did feel at risk for getting dengue and considered dengue a severe disease. However, this did not appear to influence acceptability of ITCs or RIT.Acceptability of ITCs and RIT was linked to acceptability of AaCP routine vector control activities. However, uptake and use were not always an indication of acceptability. Factors leading to acceptability may be best identified using qualitative methods, but more research is needed on the concept of acceptability and its measurement.